Correlation between machining-induced surface alterations and stress corrosion cracking susceptibility of au stenitic stainless steels - Wenqian Zhang; Yongchun Li; Hongtao Dong; Chongwen Yang; Xinli Jiang; Deyuan Lou; Huan Xue; Kewei Fang; Xuelin Wang (Journal of Materials Research and Technology, 2023)
Correlation between machined surface alterations and stress corrosion cracking (SCC) susceptibility of austenitic stainless steels is investigated. The machining-induced residual stress, roughness, micro-hardness and dislocation density were characterized and the surface/subsurface cracks were examined after SCC tests in boiling magnesium chloride solution. The results showed SCC crack initiation and early propagation were highly related to the machining-induced alterations. By establishing a quantitative relationship between the surface characteristics and surface crack density, the comprehensive impact of the residual stress, surface roughness as well as the dislocation density on SCC susceptibility is revealed. The predicted crack density is in good agreement with the measured data. As a result, the SCC susceptibility of the machined surface is described by the surface integrity properties.